THE EFFECTIVENESS OF EDUCATION IN IMPROVING THE WELFARE OF COASTAL COMMUNITIES THROUGH MARINE RESOURCE MANAGEMENT IN KAIRATU VILLAGE - Elvira Delvi Sopalauw (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to examine the effectiveness of education in improving the welfare of coastal communities through sustainable management of marine resources in Kairatu Village, West Seram Regency, Maluku Province. The research method used is a quantitative approach with survey techniques. The research instrument is a closed questionnaire distributed to 30 respondents who are coastal communities, supplemented by limited interviews to enrich the data. The analysis technique used is simple linear regression to determine the effect of the effectiveness of education (independent variable) on the level of welfare of coastal communities (dependent variable). The results of the analysis show that there is a strong, positive, and significant relationship between the effectiveness of education and community welfare, with a coefficient of determination (R²) of 0.72. This means that 72% of the variation in coastal community welfare can be explained by the effectiveness of education, while the rest is influenced by other external factors. This study shows that education that is right on target, locally based, and contextual has a major contribution in increasing community capacity in managing marine resources sustainably. Therefore, strengthening education in coastal areas is an important strategy in efforts to improve the quality of life and empower the economy of coastal communities.